2017
DOI: 10.2341/16-326-c
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performance of Different Solvent-based Dentin Adhesives With Nanofill or Nanohybrid Composites in Class III Restorations: Five Year Results

Abstract: With the exception of marginal discoloration and marginal integrity deterioration of Xeno V-bonded restorations, all four adhesive-bonded restorations exhibited good long-term results. However, adhesion strategy (such as self-etch or etch-and-rinse) is more important than the solvent content of dentin adhesive systems in the success of Class III restorations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…As the dentin bonding agent, a two-step etch-and-rinse adhesive Prime&Bond XP was used in this study due to its well-established clinical performance [56][57][58]. Moreover, the in vitro study showed an increase in its reliability (µTBS) by nearly 110% after one year of aging [59].…”
Section: Discussionmentioning
confidence: 99%
“…As the dentin bonding agent, a two-step etch-and-rinse adhesive Prime&Bond XP was used in this study due to its well-established clinical performance [56][57][58]. Moreover, the in vitro study showed an increase in its reliability (µTBS) by nearly 110% after one year of aging [59].…”
Section: Discussionmentioning
confidence: 99%